Complicaciones asociadas a la extracción de terceros molares superiores e inferiores - Guamán Moreno, Juan Fernando (2024)
In the analysis, it was identified that the most frequent complications found were injuries to soft tissues, fractures at the level of dental roots, fractures at the level of bone tissue and nerve injuries; Specifically when talking about complications of upper third molars, fractures were observed at the level of the maxillary tuberosity and oral-sinus communications; Regarding complications in the extraction of lower thirds, cases of edema, hemorrhage, root fractures, tissue lacerations, injuries to the lower dental nerve and lingual nerve were identified. Currently there are not enough recent bibliographic sources that tell us about this problem, which is why the need to carry out this research is increased, understanding that through it the topics will be correctly understood by dental professionals who will be able to find in this research, a guide on which to base yourself to identify complications in extraction procedures of upper and lower third molars; in addition to the correct protection methods. Therefore, the present study aims to analyze the complications associated with extractions of upper and lower third molars; and, which are the most frequent in both upper and lower extractions. In the same way, point out methods that will serve the dentist as a source of prevention against these complications so that in this way their professional skills are optimized and the effects on patients are reduced. The present study tries to determine the most frequent complications during the extraction of both upper and lower third molars, for which a bibliographic review has been carried out based on the reviews of 27 scientific articles, which give us different and varied indications of this surgical procedure; on topics associated with complications in the extraction of third molars and in detail what are the most frequent complications found in their extraction